2019
DOI: 10.1055/s-0039-1691524
|View full text |Cite
|
Sign up to set email alerts
|

Click Variations on the Synthesis of 2-Nitrophenyl-4-aryl-1,2,3-triazoles without Isolation of 2-Nitrophenyl Azides

Abstract: We report a series of efficient procedures to prepare 2-nitrophenyl-4-aryl-1,2,3-triazoles avoiding the isolation of potentially hazardous 2-nitrophenyl azides. An organocatalyzed azide-enolate variant allows efficient access to the target compounds while it was shown that a metal-catalyzed azide-alkyne procedure involving a preliminary ­Sonogashira coupling was feasible starting from electron-deficient aryl iodides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This was demonstrated to be a safe and simple means of accessing triazole targets as there was no need to isolate the 2-nitrophenyl azides. 11 Díez-González and co-workers (Imperial College London) reported on a one-pot, metal-free synthesis of 1,2,3-triazoles in deep eutectic solvents (the reactions involve the addition of aryl azides bearing trifluoromethyl groups with enol ethers and proceed via a cycloaddition/elimination cascade). 12 Hansen and Elumalai (The Arctic University of Norway) reported on a substantially improved synthesis of substituted benzimidazoles by condensation of 1,2-diaminoarenes and aldehydes in air (1 min) under microwave-and additive-free conditions.…”
Section: Cluster Syn Lettmentioning
confidence: 99%
“…This was demonstrated to be a safe and simple means of accessing triazole targets as there was no need to isolate the 2-nitrophenyl azides. 11 Díez-González and co-workers (Imperial College London) reported on a one-pot, metal-free synthesis of 1,2,3-triazoles in deep eutectic solvents (the reactions involve the addition of aryl azides bearing trifluoromethyl groups with enol ethers and proceed via a cycloaddition/elimination cascade). 12 Hansen and Elumalai (The Arctic University of Norway) reported on a substantially improved synthesis of substituted benzimidazoles by condensation of 1,2-diaminoarenes and aldehydes in air (1 min) under microwave-and additive-free conditions.…”
Section: Cluster Syn Lettmentioning
confidence: 99%
“…A final (mesoionic) carbene-nitrene cyclization step yielded a robust nitrogen-rich scaffold. [12][13][14] In the first step of the synthesis diversity has been shown to be easily attainable making this fluorophore family attractive from a chemical design point of view. Our observations showed that compounds of this family were more stable in solution than quinine which is used as standard for indirect measurements of quantum yields according to IUPAC 15 (no change in luminescence for solutions of our compounds stored on the benchtop while full degradation of quinine was observed).…”
Section: Introductionmentioning
confidence: 99%
“…A final (mesoionic) carbene-nitrene cyclization step yielded a robust nitrogen-rich scaffold. [12][13][14] In the first step of the synthesis diversity has been shown to be easily attainable making this https://doi.org/10.26434/chemrxiv-2024-kk8l6 ORCID: https://orcid.org/0000-0002-9446-4601 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 fluorophore family attractive from a chemical design point of view.…”
Section: Introductionmentioning
confidence: 99%